Violencias imperiales. Masacres de indios en las pampas del Río de la Plata (siglos XVI-XVIII) - Jiménez, Juan Francisco (2017)
In the pampas of the Rio de la Plata, several Indian massacres are registered since short after the re-foundation of Buenos Aires in 1580. In a context of multiple and complex interactions, the relationships between regional sovereign and politically des-centralized Indian nations and colonial administrations oscillated between diplomatic and violent ways. Native raids produced repressive reactions in charge of officials and militiamen who had interests in rural and cattle business affected by plunders, and vice-versa. Then, periodical killings repeatedly took place of native people of all sexes and ages, combatants and non-combatants -who were often not linked to the events which motivated them- as well as subsequent distribution of surviving families. The characteristics of these aggressions and their modalities and consequences over aggressed and aggressors constitute the purpose of this article, based mainly on documentation in Archivo General de Indias and Archivo General de la Nación Argentina.